Occurrence of microplastics in Russell’s snapper (Lutjanus russellii) and associated prey species in the Central Gulf of Thailand - Klangnurak, Wanlada; Prachumwong, Siriluk; Alfonso, María Belén; Nakano, Haruka; Chavanich, Suchana; Viyakarn, Voranop; Jandang, Suppakarn (My University, 2025)
Microplastic (MP) contamination in fish may occur via their feeding behavior and ingestion of contaminated prey. This study investigated the presence of MPs in the predator Lutjanus russellii (Russell’s snapper) and its prey along the Chumphon coast of the Central Gulf of Thailand. Stomach contents of L. russellii were analyzed to identify its prey species. Prey species were then sampled from the same geographical area as the predator specimens for subsequent MP analysis. The dietary habits of L. russellii classify it as a generalist carnivore, consuming a diverse range of food items, including zooplankton, crustaceans, and small fish. No significant correlation was observed between MP abundance and the weight or length of the predator fish (general linear model, p > 0.05). Black and red fibers were the predominant MP types in both predator and prey, though MP sizes varied among the sampled species. In predator stomachs, the most common polymers were acrylonitrile butadiene styrene (ABS; 26.32%), polyethylene terephthalate (PET; 21.05%), and polyester (PES; 10.53%). Conversely, prey samples were dominated by PES (17.58%), PET (15.38%), and ABS (13.19%). Notably, similarities in MP characteristics (shape, color, average size, and certain polymer types) were observed between L. russellii and Portunus sp. The detection of smaller PET fibers in L. russellii compared to Portunus sp. (Mann–Whitney U-test, p ≤ 0.05) suggests the transfer of MPs to L. russellii through the ingestion of hard-shelled crustacean prey. This study underscores the importance of examining predator–prey interactions to better understand MP contamination pathways in marine ecosystems, particularly in regions like the Gulf of Thailand, where plastic pollution is prevalent. Further research is required to assess the long-term ecological implications of MP transfer within marine food chains.
Keywords: Contamination; Food; Lutjanus; Microplastic; Thailand; Transfer